Transformasi Pembelajaran Bahasa Inggris: Menggunakan Solid Model Sebagai Media Pembelajaran di MI Fathul Jannah - Hesty Widiastuty; Syahrul Mubaroq; Adinda Aulia Rahmah; Noor Muthi’ah; Maulidina Tri Amanda; Rani Oktavia (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
This study investigated the success of a solid model teaching medium with the theme “My Farm” to enhance the English learning experience among second grade students at MIS Fathul Jannah. This medium addresses the challenge of unevenly distributed educational resources. Thirteen grade 2 students participated in this community service activity. The implementation of the activity involved three stages: preparation (survey, observation, media and material adjustment), implementation (introduction, core activities, ice breaking, and reflection), and evaluation. The results showed that the solid model media fostered active participation, created a fun learning environment, and had a positive impact on the classroom atmosphere. Future research should consider expanding the content coverage and deepening the analysis to obtain more robust data as well as innovative findings.